Srlp is crucial for the self-renewal and differentiation of germline stem cells via RpL6 signals in Drosophila testes - Yu, Jun (Cell Death Dis, 2019)
Self-renewal and differentiation in germline stem cells (GSCs) are tightly regulated by the stem cell niche and via multiple approaches. In our previous study, we screened the novel GSC regulatory gene Srlp in Drosophila testes. However, the underlying mechanistic links between Srlp and the stem cell niche remain largely undetermined. Here, using genetic manipulation of the Drosophila model, we systematically analyze the function and mechanism of Srlp in vivo and in vitro. In Drosophila, Srlp is an essential gene that regulates the self-renewal and differentiation of GSCs in the testis. In the in vitro assay, Srlp is found to control the proliferation ability and cell death in S2 cells, which is consistent with the phenotype observed in Drosophila testis. Furthermore, results of the liquid chromatography-tandem mass spectrometry (LC-MS/MS) reveal that RpL6 binds to Srlp. Srlp also regulates the expression of spliceosome and ribosome subunits and controls spliceosome and ribosome function via RpL6 signals. Collectively, our findings uncover the genetic causes and molecular mechanisms underlying the stem cell niche. This study provides new insights for elucidating the pathogenic mechanism of male sterility and the formation of testicular germ cell tumor.